2012
DOI: 10.1111/j.2047-6310.2012.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of dance‐based group exergaming in obese adolescents

Abstract: Results support the positive impact of dance-based exergaming on obese adolescents' psychological functioning and perceived competence to continue exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
172
0
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(200 citation statements)
references
References 25 publications
1
172
0
14
Order By: Relevance
“…84 PA increased in the higher contingency (behavior-consequence) AVG group but decreased in the lower contingency AVG group; the effect size of the difference was small. 91 All four studies 83,85,89,94 comparing an AVG and a non-AVG group reported positive intervention effects on the cognitive and psychosocial PA-related outcomes. Two effect sizes were small, 85 one was medium, 94 and one was large.…”
Section: Studies On the Choices Between Avgs And Sedentary Al-mentioning
confidence: 95%
See 3 more Smart Citations
“…84 PA increased in the higher contingency (behavior-consequence) AVG group but decreased in the lower contingency AVG group; the effect size of the difference was small. 91 All four studies 83,85,89,94 comparing an AVG and a non-AVG group reported positive intervention effects on the cognitive and psychosocial PA-related outcomes. Two effect sizes were small, 85 one was medium, 94 and one was large.…”
Section: Studies On the Choices Between Avgs And Sedentary Al-mentioning
confidence: 95%
“…Effect sizes for the intervention studies are presented in Table 5. Compared with a control group, 8 [83][84][85][86][89][90][91]94 of 15 intervention studies found positive effects of AVGs on PA-related outcomes (including cognitive and psychosocial variables, 83,85,89,94 behavioral outcomes, [83][84][85][86]91 and physical fitness 90 ). Two studies found AVGs increased children's PA in early sessions but not in later sessions.…”
Section: Studies On the Choices Between Avgs And Sedentary Al-mentioning
confidence: 97%
See 2 more Smart Citations
“…En esta línea, Lisón et al, (2015), comprobaron que 20 minutos de práctica competitiva (Comparando su progreso con los demás) de Xbox Kinect Adventures aumentaba la respuestas psicológicas respecto al grupo de control que solo caminaba (p <.001). Wagener et al (2012), investigó el impacto del EX Dance Dance Revolution durante 10 semanas. Encontraron que los adolescentes que utilizaban este EX mejoraban las relaciones parentales y autoconcepto respecto al grupo control.…”
Section: Resultsunclassified